THE EFFECT OF PRODUCT QUALITY, PRICE, PROMOTION AND DISTRIBUTION ON PURCHASE DECISIONS IN MEDIATED CUSTOMER SATISFACTION ON ICE CRYSTALS IN LAMONGAN - Muhtarom, Abid; Nurcholidah, Lilik; Asrori, Mohammad; Yaskun, Mohammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
At this time a lot of progress and changes that occur in the business world. The changes that occur are marked by the emergence of technological developments and the mindset of developing people who cannot be separated from the influence of globalization. With this progress and change, the community is indirectly required to be able to balance it. Companies that exist today are being faced with a condition of intense competition, only consumer-oriented companies that succeed in attracting consumer interest. The novelty of this study is that there are more variables to study compared to other studies. This type of research is quantitative with a sample size of 286 and the method used to analyze it is SEM-PLS Version 3.3.7. The test used is the outer model test, inner model test as well as mediation and hypothesis testing. Based on the results of the validity test, the loading factor value is more than 0.7 and the AVE value is more than 0.5 which is declared valid, in the reliability test the value of composite reliability and Cronbach alpha above 0.7 is declared reliablel. It can be concluded that product quality (X1), price (X2), promotion (X3), distribution (X4) on purchasing decisions (Y) is said to have a significant positive influence. In the mediation test it is said that product quality (X1), price (X2), promotion (X3), distribution of purchasing decisions (Y) through customer satisfaction (Z) is called complementary mediation.